Urban facilities management as a systemic process to achieve urban sustainability in South Africa - Boyle, Luke (Department of Construction Economics and Management, 2016)
A key challenge for urban facilities management (UFM) is to identify ways to promote sustainable urban development at a community/precinct level. One potential approach is via the application of sustainable community assessment/rating tools which have seen increased popularity amongst urban planners and developers over the past decade. This study investigates the efficacy and applicability of this approach to urban sustainability, particularly within the "developing country"context of South Africa. Furthermore, the paper suggests that the deployment of UFM in creating a management platform for urban precincts, one that focuses on the process of achieving urban sustainability within a specific locale, will deliver improved strategies for operationalising urban sustainability. Using soft systems methodology (SSM), the study aimed to establish the fundamental requirements for sustainable community development frameworks in both "developing" and "developed countries". Data was collected through semi-structured interviews with 11 key stakeholders who consisted of two main categories. Firstly, participants from private and public sector engaged in the management and development of sustainable urban precincts. Secondly, participants from NGO's that develop sustainable community rating tools. The tools included: Leadership in Engineering and Environmental Design for Neighbourhood Development (LEED-ND), Building Research Establishment Environmental Assessment Methodology for Communities (BREEAM-C), Comprehensive Assessment System for Building Environmental Efficiency for Urban Development (CASBEE-UD), EcoDistricts, Green Star Communities (GSC), and the Living Community Challenge (LCC). Interviews were conducted in both Cape Town and Vancouver; representing the "developing" and "developed"contexts respectively. It was found that the prescriptive and outcomes-based nature of assessment tools excludes "developing countries" from the sustainable community development conversation. The logical next step is to develop frameworks that offer sustainable solutions appropriate to these contexts. Findings also highlighted a need for a more robust procedural framework to manage relationships between various professionals and interest groups involved in the development of sustainable communities/precincts. This in turn provides a unified method to facilitate the achievement of urban sustainability. This research concludes that urban sustainability needs to draw upon the management principles of facilities management (FM), and more specifically UFM, to develop and assess the sustainability of communities and cities within a specific locale. Without a process-orientated method such as this, cities will continue to fall short of their sustainable imperatives.